MHD stagnation point flow of micropolar nanofluid with soret and dufour effects - Siti Norfatihah, Zulkifli; Norhafizah, Md Sarif; Mohd Zuki, Salleh; Ezzatul Farhain, Azmi (IOP Publishing, 2019)
The effect of Soret and Dufour on magnetohydrodynamic (MHD) stagnation point flow of a micropolar nanofluid over a horizontal stretching sheet is considered. A boundary condition that assumed nanoparticle flux at the plate to be zero is applied in this study. The governing equations are in partial differential equations therefore a similarity transformation variable is employed to reduce the governing non-linear partial differential equations into non-dimensional ordinary differential equations. The ordinary differential equations are computed numerically using Runge-Kutta-Fehlberg (RKF45). Validation of the result is made by comparing the present results with the previous studies. Numerical results are presented in the graphical form for temperature and concentration profile to provide a better insight of this study. It is found that, temperature profile and nanoparticle volume fraction profile increase with an increasing values of Soret and Dufour effects.